2017
DOI: 10.1051/0004-6361/201730863
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric and coronal magnetic fields in six magnetographs

Abstract: Aims. We study the long-term evolution of photospheric and coronal magnetic fields and the heliospheric current sheet (HCS), especially its north-south asymmetry. Special attention is paid to the reliability of the six data sets used in this study and to the consistency of the results based on these data sets. Methods. We use synoptic maps constructed from Wilcox Solar Observatory (WSO), Mount Wilson Observatory (MWO), Kitt Peak (KP), SOLIS, SOHO/MDI, and SDO/HMI measurements of the photospheric field and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 44 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The large spread and the high dependence on v e sin i and inclination angle makes it impossible to provide a general correction factor for the underestimation of the magnetic field by ZDI especially if one keeps in mind that our analysed stars cover only a very small fraction of the observed cool stars. The non uniform dependency on the different -modes can also be found by comparing the solar magnetograms of different solar observations as shown by Virtanen & Mursula (2017). Reiners & Basri (2009) and Morin et al (2010) showed that the averaged magnetic field measured by ZDI B V represents only 6−14 % of the total averaged magnetic field measured by Zeeman broadening B I for M dwarfs.…”
Section: Discussionmentioning
confidence: 83%
“…The large spread and the high dependence on v e sin i and inclination angle makes it impossible to provide a general correction factor for the underestimation of the magnetic field by ZDI especially if one keeps in mind that our analysed stars cover only a very small fraction of the observed cool stars. The non uniform dependency on the different -modes can also be found by comparing the solar magnetograms of different solar observations as shown by Virtanen & Mursula (2017). Reiners & Basri (2009) and Morin et al (2010) showed that the averaged magnetic field measured by ZDI B V represents only 6−14 % of the total averaged magnetic field measured by Zeeman broadening B I for M dwarfs.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore the SOLIS data set used in this work is not scaled to SPMG level. A comparison of SPMG and SOLIS observations based on harmonic expansions (Virtanen & Mursula 2017) indicates that the correct SPMG to SOLIS scaling factor would be 1.3-1.4.…”
Section: Comparing Modeled and Observed Field Evolutionmentioning
confidence: 99%
“…It is apparent that, when comparing magnetograph measurements in the context of the global solar field, pixel-by-pixel regression or histogram analyses of the photospheric flux itself, as in the study of Riley et al (2014), do not properly capture the differences between the data sets. Instead, the focus should be on the differences between the lowest-order harmonic components, as in Virtanen & Mursula (2017) and in the present study.…”
Section: Deriving the Open Flux Using Photospheric Field Maps From Di...mentioning
confidence: 96%
“…An inspection of Figure 9(b) also shows that, whichever saturation correction is adopted, the open fluxes derived from the WSO maps are systematically smaller relative to the observed IMF after ∼1998, as compared with earlier years (cf. Virtanen & Mursula 2017). This suggests that there may have been a decrease in the sensitivity of the WSO magnetograph sometime around 1998.…”
Section: Comparison With the Observed Radial Imf Variationmentioning
confidence: 99%